The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/pai.13526
|View full text |Cite
|
Sign up to set email alerts
|

Early age exposure to moisture and mould is related to FeNO at the age of 6 years

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Nevertheless, the odds of current asthma were highest among individuals belonging to class one which was characterized by higher exposure to dampness at home during childhood. Several previous meta-analyses and epidemiological studies have found a positive association between the presence of moisture and mold in homes, either measured or self-reported, and the risk of childhood asthma or markers thereof [30][31][32][33][34][35][36][37]. Our findings suggest that the presence of moisture and mold in the child's bedroom might be most important in regard to active offspring asthma at age 18.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Nevertheless, the odds of current asthma were highest among individuals belonging to class one which was characterized by higher exposure to dampness at home during childhood. Several previous meta-analyses and epidemiological studies have found a positive association between the presence of moisture and mold in homes, either measured or self-reported, and the risk of childhood asthma or markers thereof [30][31][32][33][34][35][36][37]. Our findings suggest that the presence of moisture and mold in the child's bedroom might be most important in regard to active offspring asthma at age 18.…”
Section: Discussionsupporting
confidence: 50%
“…Our findings suggest that the presence of moisture and mold in the child's bedroom might be most important in regard to active offspring asthma at age 18. Similarly, four Finnish studies have also found that moisture damage or visible mold in the child's main living areas, including the child's bedroom, were more strongly associated with asthma prevalence, persistent asthma as well as fractional exhaled nitric oxide, a marker of asthma [38], compared to moisture damage or visible mold in other areas of the house [31][32][33]39]. On the other hand, regarding mold damage remediation in houses and decreases in asthma-related symptoms, use of asthma medication in asthma patients and respiratory infections, a Cochrane review from 2015 concluded that there was only moderate-quality evidence and that more randomized studies were needed.…”
Section: Discussionmentioning
confidence: 90%
“…Venous blood samples have been taken at the age of 6 years and analyzed for specific immunoglobulin E (sIgE) to 19 common allergens by administering the Allergy Screen Test Panel for Atopy (Mediwiss Analytic). 20 , 21 The cut‐off level to define specific sensitization to 13 inhalant allergens was 0.70 kU/L. 5 …”
Section: Methodsmentioning
confidence: 99%
“…Ambient air pollution [ 13 ], household molds [ 8 ] and indoor solid fuel burning [ 9 ] are evidenced as having negative impacts on asthma outcomes. Existing studies documented that the household dampness and mold occurred in 1/4 of children’s houses in southern China, and the presence of dampness and mold at home was associated with an increased risk of developing asthma (OR = 1.31, 95% CI: 1.08–1.59) in children [ 14 , 15 ]. A study conducted in Lanzhou, China, has illustrated that paternal asthma (OR = 3.143, p < 0.01) and maternal asthma (OR = 3.542, p < 0.01) were both associated with an increased prevalence of childhood asthma [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the studies on respiratory diseases and their influencing factors are mostly focused on western countries, as well as mainland China in areas with developed economies or large population [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]; only a few studies have been conducted in areas that are economically underdeveloped or have a low population density [ 8 ]. This situation is neither conducive to rationally analyze the incidence of respiratory diseases nor beneficial to provide scientific evidence for reducing the risk of respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%